Analisis Pengaruh Struktur Kepemilikan Institusional, Firm Size, Leverage, Dan Pertumbuhan Perusahaan Terhadap Profitabilitas Pada Perusahaan Non-Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014 - Sari, Ira Yunita; , Zulfa Irawati, S.E., M.Si (2016)
This study aimed to analyze the significant influence of Institutional Ownership Structure, Firm Size, Leverage and Corporate Growth to Profitability In Non-Banking Companies listed on the Indonesia Stock Exchange in 2011-2014. The population in this study using the Company's Non-Pebankan listed on the Indonesia Stock Exchange in 2011-2014. Samples are 4 Non-Banking Companies listed in LQ45 Index, where the sample method used was purposive sampling is a sampling method that takes an object with certain criteria. Data analysis method used is multiple linear regression analysis and hypothesis testing using t-statistic, the F-statistic and the coefficient of determination. From the analysis during the observation period t test results showed that the variables Institutional Ownership Structure and Growth no significant effect on profitability, while the Firm Size and Leverage significant effect on profitability. In addition Leverage variables are variables that most influence on profitability. The results of the F test analysis found that the variable Institutional Ownership Structure, Firm Size, Leverage and Growth Company jointly significant effect on profitability. The results of the analysis of the coefficient of determination (R ²) were obtained Adjusted R square (R ²) of 0.497, this shows that the profitability can be explained by the variable Institutional Ownership Structure, Firm Size, Leverage and Corporate Growth amounted to 49.7%, while the rest described 50 , 3% are influenced by other factors beyond the variables studied.